Artificial hyperventilation normalizes haemodynamics and arterial oxygen content in hypoxic rats - De Villalobos, Diego; Laserna, Andres; Fowler, Cosmo; Cuenca, John A.; Martin, Peyton; Guindani, Michele; Dong, Wenli; Gutstein, Howard B.; Price, Kristen J.; Nates, Joseph L. (Anaesthesiology Intensive Therapy, 2021)
Background: Although humans are capable of enduring critically low levels of oxygen, many hypoxaemic patients die despite aggressive therapies. Mimicking the physiological hyperventilation necessary to survive extreme hypoxic conditions could minimize the derangements caused by acute hypoxic-hypoxia. The objective of this study was to measure the haemodynamic-biochemical response to artificially induced hyperventilation in hypoxic rats. Methods: Twenty-four deeply anaesthetized and mechanically ventilated rats were allocated to 3 groups: control (n = 5, FiO2 = 1); hypoxic spontaneously hyperventilating (n = 10, FiO2 = 0.08); and hypoxic artificially induced hyperventilation (n = 9, targeting PaCO2 = 10 mm Hg, FiO2 = 0.08). We compared the spontaneously and artificially hyperventilating groups. P-values < 0.01 were considered statistically significant. Mean arterial pressure (MAP) and serum chemistry were measured for 180 minutes. Results: The control group remained stable throughout the experiment. The hypoxic groups developed profound hypotension after the decrease in FiO2. However, the artificially induced hyperventilated rats recovered their MAP to levels higher than the spontaneously hyperventilating group (117.1 ± 17.2 vs. 68.1 ± 16.0, P = 0.0048). In regard to the biochemical derangements, even though the serum lactate and PaO2 were not different among the hypoxic groups, the artificially hyperventilated group achieved significantly higher SaO2 (94.3 ± 3.6 vs. 58.6 ± 9.6, P = 0.005), pH (7.87 ± 0.04 vs. 7.50 ± 0.13, P = 0.005), and CaO2 (17.7 ± 2.6 vs. 10.2 ± 1.3, P = 0.005) at 180 minutes. Conclusions: Artificially induced hyperventilation led to the correction of arterial oxygen content, severe serum chemistry, and haemodynamic derangements. These findings may represent a novel rescue manoeuvre and serve as a bridge to a permanent form of support, but should be further studied before being translated to the clinical setting.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Artificial respiration; Critical illness; Hyperventilation; Hypocapnia; Hypoxia; Respiratory insufficiency